Enhancing cross-cultural applicability in recovery colleges: A global Delphi study protocol - Yasuhiro Kotera; Tesnime Jebara; Vanessa Lawrence; Simran Takhi; Amy Ronaldson; Simon Lawrence; Vanessa Kellermann; Agnieszka Kapka; Peter Bates; Claire Henderson; Mike Slade (PLoS ONE, 2025)
Background Recovery Colleges (RCs) offer an innovative model of mental health support that blends co-production with adult learning to promote personal recovery and social inclusion. While evidence supports their effectiveness, most RC research and practice have been developed in Western contexts, raising concerns about cross-cultural applicability. The RECOLLECT Change Model (RCM) and RECOLLECT Fidelity Measure (RFM) were developed in England to characterise RC mechanisms and assess fidelity. Our previous studies have identified cultural influences on the RC operational model, however how to address these influences remains unknown. Given the increasing global interest in RCs, the aims of this study are to (a) identify the level of cultural influence on the RCM mechanisms and RFM items, and (b) provide recommendations to inform cross-cultural applicability of RCM and RFM. Methods This global Delphi study follows Belton’s six-step methodology and uses a decentring approach to cross-cultural research that seeks to extend the relevance of tools developed in a single culture to multiple cultural contexts. Experts will be recruited via the RECOLLECT International Research Consortium, covering 31 countries across six continents. We aim to recruit approximately 100 panellists with at least three years’ RC experience. Data collection will occur via Microsoft Forms across iterative Delphi rounds. Panellists will rate the importance and cultural difficulty of RCM and RFM items, provide feedback on culturally aligned response types, and suggest revisions for improved cultural fit. Quantitative data will be analysed using non-parametric statistics and a collapsed three-point Likert scale to address cross-cultural response bias. Qualitative responses will be analysed using descriptive content analysis informed by Hofstede’s cultural dimension theory. Member checking will be conducted after the final round to enhance trustworthiness. Discussion This study will identify which RCM and RFM components are cross-culturally applicable and which require adjustment, contributing to the balance between fidelity and fit in mental health approaches. By developing culturally informed recommendations, this study aims to expand the accessibility and relevance of RC frameworks across diverse settings. Findings will benefit RC practitioners, researchers, and policymakers seeking to improve service delivery and recovery outcomes in culturally meaningful ways.